Facilitators of and barriers to success in nursing internship programs: A qualitative study of interns' and faculty members' perspectives. (February 2022) - Bahari, Ghareeb; Alharbi, Fawaz; Alharbi, Othman
Abstract: Background: Through internship programs, nursing students learn information and skills in multiple hospital departments. Internships can also help with transitioning from student roles to graduate roles. However, the factors contributing to successful clinical internships in different education and health systems have not yet been sufficiently explored. Objective: The purpose of this study was to explore the factors that contribute to successful clinical internships in both public and private hospitals in Saudi Arabia. Design: This study uses a qualitative descriptive design. Setting: Due to precautionary measures for COVID-19 and the inclusion of participants from different locations across Saudi Arabia, this study was conducted virtually. Participants: The study was conducted with a purposive sample of 16 nursing interns and four instructors. Methods: Data were collected via semi-structured interviews to provide a wide variety of perspectives from nursing students and instructors. Each interview was recorded, transcribed verbatim in Arabic, and then translated into English. Collected data were analyzed using a thematic analysis approach. Results: Three facilitators of success and four barriers to success emerged in the study. Facilitators of success included the program curriculum, hospital internship program, and contribution to the nursing board exam. Barriers to success were as follows: exploitation, lack of self-confidence, lack of incentives, and the long duration of the programs. Conclusions: The findings of this study could contribute to the creation of more effective clinical internship. It is recommended that clinical internship programs be enhanced and that appropriate support be given to nursing students.